Construction of RNA Interference Vector to Silence Aluminum Tolerance Gene Candidate in Rice cv Hawara Bunar - Windarti Wahyuningtyas; Miftahudin Miftahudin; Utut Widyastuti; Aris Tjahjoleksono (Bogor Agricultural University, Indonesia, 2016)
One of the aluminum (Al) tolerance gene candidates, namely B11 gene, has been successfully isolated from Al-tolerant rice cv Hawara Bunar. However, the role of the gene in Al tolerance in rice has not been known. RNA interference (RNAi) technique is an effective tool to examine the biological function of the target gene in plant. The objective of the research was to construct RNAi recombinant vector carrying untranslated region of the B11 gene. RNAi recombinant vector carrying 195 bp sized 3′UTR_B11 fragment as a double-stranded RNA (dsRNA) trigger has been successfully constructed using GATEWAY™ cloning technology, pENTR™/D-TOPO® as a shuttle vector, and pANDA vector as a destination vector. RNAi construct was successfully introduced into Agrobacterium tumefaciens AgL0, and has been infected to rice cv Hawara Bunar. Analysis of putative transgenic rice showed eight of 20 plants were transgenic carrying the B11-RNAi construct.